2021
DOI: 10.1074/jbc.ra120.015997
|View full text |Cite
|
Sign up to set email alerts
|

ABCA13 dysfunction associated with psychiatric disorders causes impaired cholesterol trafficking

Abstract: ATP-binding cassette subfamily A member 13 (ABCA13) is predicted to be the largest ABC protein, consisting of 5058 amino acids and a long N-terminal region. Mutations in the ABCA13 gene were reported to increase the susceptibility to schizophrenia, bipolar disorder, and major depression. However, little is known about the molecular functions of ABCA13 or how they associate with psychiatric disorders. Here, we examined the biochemical activity of ABCA13 using HEK293 cells transfected with mouse ABCA13. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…The ABC family genes encode transporters that utilize the hydrolysis of ATP as the energy source to transport the substrates across the membrane to maintain the normal physiological functions in various tissues [30]. The ABCA13 encodes a large protein of 5058 amino acids and internalizes cholesterol and gangliosides from the plasma membrane to intracellular vesicles [31]. Knight and colleagues were the first to report the significant association of rare mutations of ABCA13 with SZ, BD, and major depression [32].…”
Section: Discussionmentioning
confidence: 99%
“…The ABC family genes encode transporters that utilize the hydrolysis of ATP as the energy source to transport the substrates across the membrane to maintain the normal physiological functions in various tissues [30]. The ABCA13 encodes a large protein of 5058 amino acids and internalizes cholesterol and gangliosides from the plasma membrane to intracellular vesicles [31]. Knight and colleagues were the first to report the significant association of rare mutations of ABCA13 with SZ, BD, and major depression [32].…”
Section: Discussionmentioning
confidence: 99%
“…Using RNA-Seq, we previously observed that the cholesterol route (bta04977) was dysregulated in the ileocecal valve (ICV) of cows with diffuse lesions versus the control group with four upregulated genes matching this route ( APOA1, APOC3, APOA4, APOB ) 34 . In addition, the top upregulated gene in peripheral blood of animals with focal lesions versus control cows was the ATP-Binding Cassette Subfamily A Member 13 ( ABCA13 ), a gene that accelerates cholesterol internalization and accumulation in intracellular vesicles 34 , 44 , 45 . In agreement with our data, recent evidence suggests that MAP-infected macrophages accumulate intracellular cholesterol droplets and depict a foam cell phenotype during infection providing an enriched environment for MAP survival 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Using RNA-Seq, we previously detected that the cholesterol route (bta04977) was dysregulated in the ICV of cows with diffuse lesions versus the control group with four upregulated genes matching this route (APOA1, APOC3, APOA4, APOB) [31]. In addition, the top upregulated gene in peripheral blood of animals with focal lesions versus control cows was the cassette subfamily A member 13 (ABCA13), a gene that accelerates cholesterol internalization and accumulation in intracellular vesicles [31][32]41]. In agreement with our data, recent evidence suggests that MAP-infected macrophages accumulate intracellular cholesterol droplets and depict a foam cell phenotype providing an enriched environment for MAP survival [42][43].…”
Section: Discussionmentioning
confidence: 99%